Transforming Classroom Norms as Social Change: Pairing Embodied Exercises with Collaborative Participation in the WGS Classroom (with Syllabus) - Jones, Cara E (Radical Teacher, 2017)
This article explores tensions between critical feminist pedagogy and the neoliberal corporate university, asking how engaging the body and redistributing student agency highlights larger questions of power that haunt the academy as a whole. Including specific embodied exercises used in WGS classrooms, this essay argues that as students and professors engage within an increasingly corporate university system, embodied activities that incorporate the body as a site of learning and critical analysis can access situated knowledges while projects that de-center power and responsibility are viewed with skepticism. I attribute this discrepancy to the neoliberal structure in which we teach and learn, arguing that we need to value and make visible the labor that goes into critical pedagogy.